2011
DOI: 10.1007/s00280-011-1753-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of sorafenib in combination with 5-fluorouracil infusion in advanced hepatocellular carcinoma

Abstract: The results show an encouraging disease control rate, time to progression, and overall survival. The combination of sorafenib and 5-fluorouracil was feasible, and the side effects were manageable for patients carefully selected for liver function and performance status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 27 publications
0
40
0
2
Order By: Relevance
“…In a phase Ⅱ trial with 39 advanced HCC patients, sorafenib in combination with 5-fluorouracil infusion showed an encouraging disease control rate with the stable disease (SD) rate of 46.2% for a median duration of 16.2 mo, median TTP of 8 mo and OS of 13.7 mo [46] . Metronomic chemotherapy using tegafur/uracil has been shown to enhance the anti-tumor effect of antiangiogenic agents in preclinical models.…”
Section: Combinational Therapy With Sorafenibmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase Ⅱ trial with 39 advanced HCC patients, sorafenib in combination with 5-fluorouracil infusion showed an encouraging disease control rate with the stable disease (SD) rate of 46.2% for a median duration of 16.2 mo, median TTP of 8 mo and OS of 13.7 mo [46] . Metronomic chemotherapy using tegafur/uracil has been shown to enhance the anti-tumor effect of antiangiogenic agents in preclinical models.…”
Section: Combinational Therapy With Sorafenibmentioning
confidence: 99%
“…In a multicenter phase Ⅱ So.LAR. study with 50 ad- Combinational therapy 5-fluorouracil plus sorafenib [46] Phase Ⅱ 39 SD: 46.2%; median TTP: 8 mo; OS: 13.7 mo Tegafur/uracil plus sorafenib [47] Phase Ⅱ 53 Median PFS: 3.7 mo; median OS: 7.4 mo Octreotide plus sorafenib [48] Phase Ⅱ (So.LAR.) 50 SD: 66%; median TTP: 7.0 mo; median OS: 12 mo Doxorubicin plus sorafenib vs doxorubicin plus placebo [50] Phase Ⅲ 47 vs 49 Median TTP: 6.4 mo vs 2.8 mo; OS: 13.7 mo vs 6.5 mo; PFS: 6.0 mo vs 2.7 mo Erlotinib plus sorafenib vs erlotinib plus placebo [53,54] Phase Ⅲ (SEARCH) 362 Median TTP: 3.2 mo vs 4.0 mo; OS: 9.5 mo vs 8.5 mo Second-line treatments Sunitinib [55] Retrospective analysis 11 SD: 40%; median TTP: 3.2 mo Brivanib [56] Phase Ⅱ 46 SD: 41.3%; RR: 4.3%; DCR: 45.7%; median OS: 9.79 mo Tivantinib vs placebo [6] Phase Ⅱ 71 vs 36 Progressive disease: 65% vs 72%; TTP: 1.6 mo vs 1.4 mo Gemcitabine plus oxaliplatin [59] Retrospective analysis 18 Overall RR: 18.8%; SD: 18.8%; median PFS: 3.2 mo; OS: 4.7 mo Erlotinib plus bevacizumab [61] Phase controlled arm in this trial, the encouraging outcome was unable to justify that the efficacy was from sorafenib alone or the synergism with doxorubicin.…”
Section: Combinational Therapy With Sorafenibmentioning
confidence: 99%
“…Analysis of the cost-effectiveness of the treatments under investigation should also be an important consideration in future trials. Hsu et al [166] Tegafur/uracil Prospective phase Ⅱ 53 7.4 57 3.7 Prete et al [161] Long-acting octreotide Prospective phase Ⅱ 50 12 76 7 Abou-Alfa et al [165] PR- 104 Prospective phase Ⅰ 14 NR 50 NR Lee et al [164] S-1 fluoropyrimidines Prospective phase Ⅰ 20 10.4 52.9 3.9 Petrini et al [163] 5-Fluorouracil Prospective phase Ⅱ 39 13.7 48.7 7.5 Table 3 Combined sorafenib plus systemic anticancer therapy for unresectable hepatocellular carcinoma DCR: Disease control rate; NR: Not recorded; OS: Overall survival; PFS: Progression-free survival.…”
Section: Resultsmentioning
confidence: 99%
“…Several combinations of sorafenib with systemic chemotherapeutic agents have been evaluated, including sorafenib with doxorubicin [160] , octreotide [161] , oxaliplatin [162] , 5-fluorouracil [163] , S-1 fluoropyrimidines [164] , PR-104 [165] , tegafur/uracil [166] , cisplatin and gemcitabine [167] , and AVE 1642 (a human monoclonal antibody inhibiting the insulin-like growth factor-1 receptor) [168] (Table 3). Other ongoing phase Ⅱ trials include the combination of sorafenib with gemcitabine/ oxaliplatin [169] , modified FOLFOX [170] , or capecitabine/ oxaliplatin [171] .…”
Section: Sorafenib and Systemic Chemotherapymentioning
confidence: 99%
“…In HCC, Petrini et al (10) reported that treatment with a combination of sorafenib and 5-FU improved the efficacy of systemic treatment in advanced HCC without side effects.…”
Section: Introductionmentioning
confidence: 99%